Cardanol-based green nanovesicles with antioxidant and cytotoxic activities. Issue 16 (1st November 2016) - Behalo, Mohamed Sayed; Bloise, Ermelinda; Carbone, Luigi; Sole, Roberta Del; Lomonaco, Diego; Mazzetto, Selma Elaine; Mele, Giuseppe; Mergola, Lucia
ABSTRACT: This manuscript describes the preparation of green nanovesicles by using cardanol as renewable starting material with embedded minor amounts of phthalazines, a class of heterocyclic bioactive compounds. The nanovesicles were prepared by stirring induced self-assembly in aqueous medium without involvement of any organic solvent. Dynamic light scattering studies and transmission electron microscopy revealed the formation of nanostructure with an average diameter in the range of 227–375 nm and a well defined spherical morphology. Potential antioxidant activity of nanovesicles were evaluated for the first time by 2, 2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) scavenging assay and bleomycin-dependent DNA damage. Moreover, their cytotoxic effects were also investigated by 3-[4, 5-dimethylthiazole-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay on different tumour cell lines. Unloaded nanovesicles showed moderate antioxidant and antitumoural activity that was further enhanced particularly by embedding the 2-[4-(4-Hydrazinophthalazin-1-yl)-phenyl]-isoindole-1, 3-dione compound.